Differentiating the roles of intolerance of uncertainty and negative beliefs about worry across emotional disorders - Penney, Alexander; Rachor, Geoffrey S.; Deleurme, Kendall A. (My University, 2020)
Background: Researchers have examined intolerance of uncertainty (IU) and negative beliefs about worry (NBW) in emotional disorders. However, the distinct relationships of IU and NBW remain unclear. We examined IU and NBW across emotional disorders, controlling for overlapping symptoms. We also explored prospective and inhibitory IU. Methods: A sample of 565 undergraduates completed measures of IU and NBW, as well as measures of generalized anxiety, depression, social anxiety, panic, post-traumatic stress, obsessive-compulsive, and illness anxiety disorder symptoms. Regression analyses were used to determine which factors were uniquely associated with symptoms of each disorder. Results: Both IU and NBW were associated with generalized anxiety and social anxiety disorder symptoms. IU was also associated with obsessive-compulsive disorder symptoms and negatively associated with panic disorder symptoms. NBW was also associated with depression. Neither IU now NBW were associated with post-traumatic stress or illness anxiety disorders. Prospective and inhibitory IU also had differential associations with the emotional disorders. Conclusions: Our results indicate that IU and NBW, while transdiagnostic, are differentially associated with emotional disorder symptoms. Our results also support the discriminant validity of prospective and inhibitory IU.
Keywords: anxiety disorders; depression; emotional disorders; intolerance of uncertainty; metacognition; negative beliefs about worry